Service Quality and Satisfaction with City Bus Public Transport, Kota Kinabalu Sabah - Ali Mohamed, Abdullahi; Yau Giou, Chong; Billa, Lawal; Ahmadullah Farooqi, Mohd. (International Journal of Engineering and Technology, 2018)
The urban public transportation is an important network system that many urban residences have come to rely on for accessibility and linkage to key urban areas. Although in many urban centers, private transport services is also a preferred mode of transport for many people, however, the significance of public transport remains a perceived need of the city from the standpoint of efficient and timely link between urban areas, control of traffic congestion, and impact on the urban air quality. For the public to maintain their patronage in public transport, reasonable public satisfaction with the services offered is indispensable. Kota Kinabalu city bus is a government-operated bus company started in 2009, but is gradually loosing public interest with low patronage, resulting in increase in personal vehicle traffic. This study aims to understand the reasons for low user patronage of city bus service by investigating the efficiency and quality of service provided. Both quantitative and qualitative data were collected using questionnaire survey and open ended interview. Data is analyzed using inferential statistics analysis and factor analysis. Findings reveals that majority of the users are female of Malaysia nationality in age group 18-24 years and predominantly from low-income group. Overall users rated satisfaction is low because poor services in key area such as Disabled-friend Facility, Bus Network Coverage, Overcrowding and Vehicle Cleanliness. Comfort and Safety were also a major area of concern. It was evident from the study that the users are willing to pay more for improved quality City but. It can thus be inferred that the users of public bus service are not necessarily looking for cheap services but will appreciate improved services at the reasonable priceÂ Â